Adolescent Lifestyle as a Risk Factor for Diabetes - Nofi Susanti; Syakira, Salsabila; Ningtias, Afri; Purba, Elsa Yoreina (PROMOTOR, 2024)
Diabetes mellitus is a non-communicable disease that can be caused by lifestyle factors or habits. Along with the development of the times and technology that is very concentrated, many people have begun to change their lifestyle to be more practical, especially in adolescents. Teenagers often prefer to consume modern foods such as junk food, instant food, and sweet drinks such as soda and boba without seeing the high fat and sugar content in them, coupled with lack of physical activity, and unbalanced sleep patterns. If this lifestyle is carried out continuously for years, the development of adolescents who should still be in their growth period will be hampered, another risk is the emergence of various diseases that adolescents do not realize are the result of their lifestyle habits. This study aims to determine the relationship between adolescent lifestyle habits and the risk of diabetes. This data search uses literature review research methods derived from Google Scholar.